EFFECT OF TREATMENT OF METABOLIC ACIDOSIS IN CHRONIC KIDNEY DISEASE (CKD) : A SYSTEMATIC REVIEW - Nur Amelia , Devita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Plasma anions outweigh cations in metabolic acidosis. Metabolic acidosis may aggravate renal impairment. Sodium bicarbonate may help. Sodium bicarbonate in maintenance dialysis produces metabolic alkalosis. In chronic renal illness, sodium bicarbonate may worsen vascular calcifications. Aim: This article examines the link between effect of treatment of metabolic acidosis in chronic kidney disease (CKD). Methods: By evaluating the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 standards, this study demonstrated that it met all of the requirements. This enabled the researchers to ensure that the study was as up to date as feasible. Publications published between 2000 and 2023 were included in the search strategy, which included a variety of electronic reference databases (including Pubmed and SagePub). We did not consider review papers, duplicate publications, or half completed articles. Result: In the PubMed database, the results of our search brought up 388 articles, whereas the results of our search on SagePub brought up 201 articles. The results of the search conducted for the last year of 2013 yielded a total of 48 articles for PubMed and 22 articles for SagePub. In the end, we compiled a total of 25 papers, 17 of which came from PubMed and eight of which came from SagePub. We included eight research that met the criteria. Conclusion: The findings of the current investigation demonstrated that supplementation with alkali had a beneficial effect on preserving LBM and GFR in patients with CKD.